Evidence for coherent curvature radiation in PSR J1645−0317 with disordered distribution of polarization position angle. Issue 1 (20th February 2023) - Mitra, Dipanjan; Melikidze, George I; Basu, Rahul
ABSTRACT: The diverse polarization properties in pulsars are in conflict with applying a unique emission mechanism to the population. The polarization position angle (PPA) traverse in most pulsars shows an S-shaped curve that can be interpreted using the rotating vector model (RVM) as the radio emission being directed either parallel or perpendicular to the divergent magnetic field lines and argues for a coherent curvature radiation mechanism from charge bunches in a strongly magnetized pair plasma. However, in a subset of pulsars the radio emission is significantly depolarized and the PPA shows a complex pattern which cannot be explained using RVM. We propose that even in such cases the highly polarized time samples in the single pulses should follow the RVM with possibly two parallel tracks separated by 90°. We have investigated PSR J1645−0317, with complex PPA traverse, and showed new evidence that considering only the highly polarized time samples in the single pulses, the PPA distribution clearly follows the RVM. We conclude that this strongly favours the coherent curvature radiation mechanism to be universally applicable in the pulsar population.